Change point detection in recent hydropower generation in Romania. Issue 1 (January 2021) - Neagoe, A; Tică, E-I; Popa, F; Popa, B
Abstract: In Romania, about thirty percent of the installed capacity in National Power Grid and a third of the electricity generation is in hydropower plants. Thus, any aspect related to this form of renewable energy source is very valuable. Chronological records of yearly hydropower generation in Romania represent a time series that can be statistically analysed. The aim of this work is to determine the trend of this time series and, also, to locate the change points, where the time series has significant change. The period analysed is from 1980 to the present. To determine the change point of this time series, the Pettitt method was applied.